Design, synthesis, and biological activity evaluation of campthothecin‐HAA‐Norcantharidin conjugates as antitumor agents in vitro. (31st October 2018) - Wang, Xian H.; Huang, Mei; Zhao, Chang K.; Li, Chan; Xu, Lang
Abstract : Three components of Camptothecin, hydroxyacetic acid, and functionalized norcantharidins were constructed together to form a novel series of camptothecin derivatives in a good yield. The synthesized campthothecin‐HAA‐norcantharidin conjugate pro‐drugs could suppress cancer cell growth in vitro. These conjugated pro‐drug molecules possess therapeutic potential as novel bi‐functional conjugates platforms for cancer treatment. Abstract : Three components of Camptothecin, hydroxyacetic acid, and functionalized norcantharidins were constructed together to form a novel series of camptothecin derivatives in a good yield. The synthesized campthothecin‐HAA‐norcantharidin conjugate pro‐drugs could suppress cancer cell growth in vitro. These conjugated pro‐drug molecules possess therapeutic potential as novel bi‐functional conjugates platforms for cancer treatment.